Wings Against Empire: Postcolonial Allegory and Subaltern Resistance in García Márquez’s “A Very Old Man with Enormous Wings” (Journal of Asian Development Studies, 2025)
This study offers a postcolonial reading of Gabriel García Márquez's "a very old man with enormous wings" (1955), exploring how the text allegorizes colonial systems of othering, commodification, and resistance. The story's portrayal of a frail winged old man—captured, displayed, and eventually discarded by a village—mirrors the historical trajectory of colonized peoples: first feared as the "other," then exploited as curiosities, and finally abandoned once their perceived utility wanes. Drawing on the theoretical frameworks of Edward Said, Homi K. Bhabha, and Gayatri Chakravorty Spivak, this research examines how the villagers' treatment of the older man enacts Orientalist representation, silences the subaltern voice, and seeks to erase the destabilizing hybridity he embodies. Through close textual analysis within a qualitative paradigm, the study argues that Márquez's magical realism functions as a decolonial aesthetic, unsettling Eurocentric epistemologies and reclaiming space for marginalized worldviews. Positioned within a pedagogical context as a lecturer in English at Abdul Wali Khan University, Mardan, this inquiry foregrounds how literature from the global south disrupts Eurocentric hierarchies and fosters critical consciousness about cultural imperialism. Ultimately, the story critiques colonial power structures while envisioning liberation through the older man's final, transcendent flight.